VEGETATIVE RAW MATERIAL FOR RECEPTION OF THE PETROLEUM PRODUCTS AND ENERGY SECURITY OF REPUBLIC OF MOLDOVA - Duca G.; Krachune A. (Problems of the Regional Energetics, 2007)
The problem of increase of energy security of Republic Moldova is examined due to use of own power resources. Application of a biodiesel engine, bioethanol in mixes with traditional kinds of fuel (diesel fuel and gasoline) is possible without updating a design of existing engines of internal combustion and can be economic for agriculture and on transport. Results of experiments on definition износоустойчивости lubricants received of vegetative raw material of local manufacture are resulted. Use of bioethanol as the additive to gasoline will lower hisits cost, will reduce consumption of gasoline to 15-20 % and will allow to reduce considerably harmful emissions in an atmosphere, ecological safety that will favorably be reflected on health of the population will be raised. Manufacture of lubricants with use рапсового oils also will allow to receive serious economic benefit.